MORPHOMETRIC INDICATORS OF SYUNIK REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
On the basis of large-scale maps there has been done an attempt to analyze morphometric indicators of Zangezur contour (hypsometry, exposition of slopes, density and depth of surface breaking-up). It is proved, that not only litologic composition of rocks, but also tectonic movements of the contour, influence on the amount of morphometric indicators. The study of morphometric indicators of Zangezur contour is of great importance for planning and designing of engineering structures.
Keywords: Syunik Region; Zangezur contour; litologic composition of rocks; hypsometry; exposition of slopes; density and depth of surface breaking-up